Attitudes toward a flagship caprid, the endangered Cretan agrimi - Vasilios Liordos; Georgios Aggelioudakis; Vasileios J. Kontsiotis (Euro-Mediterranean Journal for Environmental Integration, 2026)
The agrimi ( Capra aegagrus cretica ), endemic to Crete, Greece, is threatened by illegal hunting and hybridization with domestic goats. Wildlife conservation cannot succeed without incorporating human dimensions into management plans. Therefore, we surveyed the attitudes and emotions of 301 Cretans toward the agrimi using face-to-face interviews. Most participants (64.1–98.3%) viewed the agrimi as important and worthy of protection (high conservation attitude) and accepted management strategies, including controlling illegal hunting (93.0%) and reintroduction (74.1%) (high management attitude). In contrast, most participants (59.5–75.4%) did not want agrimi kept in zoos, farmed, or hunted (low utilization attitude). Most participants found the agrimi attractive (82.1%) and were not afraid of it (72.8%). Structural equation modeling showed significant relationships ( p β = 0.431), while utilization was negatively associated with management ( β = −0.078). Farmers had higher utilization ( β = 0.129) but lower management attitudes ( β = −0.127) than nonfarmers. Rural residents had higher utilization ( β = 0.153) and lower conservation attitudes ( β = −0.185) than urban residents. Consumptive recreationists supported conservation ( β = 0.129) and utilization ( β = 0.116), whereas nonconsumptive recreationists supported conservation ( β = 0.156) and management ( β = 0.195) but not utilization ( β = −0.121). Females showed higher conservation attitudes ( β = 0.119) and lower utilization attitudes ( β = −0.150) than males. Older participants focused more on utilization ( β = 0.139) and less on management ( β = −0.118) and conservation ( β = −0.089) than younger participants. Participants who considered the agrimi attractive held positive conservation ( β = 0.536) and management ( β = 0.378) attitudes and negative utilization attitudes ( β = −0.231). Findings could be integrated into environmental policies and strategies to promote the well-being of the agrimi and the interdependent social and natural systems.